Moments that matter: educational entanglements and ecologies of action. Issue 1 (2nd January 2017) - Dowd, John
ABSTRACT: In this article, I argue that "the freedom to make and remake our cities and ourselves" is intimately entangled with processes of education. 1 To understand this relationship, we need to articulate more fully the role and state of teaching and learning both within and outside of academe. I argue that education allows for a negotiation of one's relationship within broader ecologies of action, which comprise constellations of power (and their correlate ideologies), discourses, bodies, material sites, and practices. More specifically, I elucidate three primary ways that education might serve as a powerful mode of tactical resistance to the deleterious effects of neoliberalist regimes and their exclusionary agendas: (1) research and rejuvenated public intellectualism; (2) understanding teaching as the nurturing of capacities rather than as a conduit for information transfer; and (3) centering education on the cultivation of a learning mode. 2